EFFECT OF BOTANICALS FOR ANTIFUNGAL ACTIVITY AGAINST PENICILLIUM SPECIES IN SWEET ORANGE (Journal of Plant Disease Sciences, 2017)
Green mould caused by the pathogen sp. is the most economically Penicillium important post harvest disease of sweet orange fruits. Studies were conducted on the management of the disease using botanicals. Out of the 25 botanicals, plant extracts of eucalyptus ( ), neem ( ), zimmu Eucalyptus oblique AzadirachtaindicaA.Juss. ( ) were found to be effective against the pathogen at 2.5, 5 and 10% Allium sp concentration under laboratory conditions. Fruits dipped in the above plant extracts prior to inoculation also showed maximum control at 10% concentration. It was inferred from this study that eucalyptus was most effective under v showing in itro 83.70 per cent inhibition over control at 10 per cent concentration and least disease incidence of 33.33% was recorded by the fruits treated with Eucalyptus.
Keywords: Sweet orange, botanicals, antifungal activity, Penicillium spp.